Between the ice of the Orkney Islands: filming the beginnings of the Antarctic overwintering tradition. Issue 2 (3rd July 2019) - Fontana, Pablo Gabriel
ABSTRACT: In 1927, the Argentine José Manuel Moneta, head of the Meteorological Station at Laurie Island, filmed the documentary Entre los hielos de las islas Orcadas (Among the Ice of the Orkney Islands) . Through a socio-historical analysis of its representations, this paper considers the film as a cinematic document of a new Antarctic social tradition, which includes a series of practices internalised by scientists overwintering on permanent stations. Since 1904, these practices were institutionalised through the logistical and scientific crews that are relieved yearly. Those practices are some of the most characteristic features of contemporary Antarctic science. The film shows a new form of human activity in Antarctica in a way that differentiates it from the most characteristic elements of the Heroic Era. In this new era, a scientific station becomes the space where scientific activity develops over 12 months, repeating itself each year with a new understanding of time in a cyclical way and a set of social practices that continue through to the present.